Pendidikan Inklusif dan Teknologi Asistif: Optimalisasi Media Digital untuk Siswa Berkebutuhan Khusus - Ardi, Suratman; Hilmi, Izzatul (MANDALA WIDYA: Jurnal Ilmu Pendidikan, 2025)
Inclusive education embodies the principles of social justice by ensuring that all pupils, including those with special educational needs, are provided with equitable access to meaningful learning opportunities. In the contemporary digital era, the strategic use of assistive technologies and digital media has become increasingly vital for cultivating learning environments that are not only inclusive but also adaptive and capable of supporting pupils’ independence. These technologies offer tools that can accommodate diverse learning profiles, reduce barriers to participation, and enhance pupils’ confidence in engaging with curricular content. This study seeks to examine the integration of assistive technologies and digital media in facilitating learning for pupils with special educational needs. Employing a systematic literature review, the research synthesises empirical findings from a range of studies that investigate how technology is utilised within inclusive educational settings. The review demonstrates that the thoughtful implementation of digital and assistive technologies can significantly improve accessibility, increase motivation, foster autonomy, and strengthen social interaction among pupils. Furthermore, the findings highlight that the successful adoption of such technologies requires cohesive collaboration among teachers, technology developers, school administrators, and policymakers. This collaborative approach is essential to ensure both the effectiveness and the long-term sustainability of assistive technology initiatives in inclusive education systems.